Zur Stellung des Deutschen auf dem europäischen Arbeitsmarkt - Joanna Szczęk (Linguistische Treffen in Wrocław, 2024)
For some time now, there has been a trend for German studies programs to be adapted to the needs of students on the one hand, and to the needs of the job market on the other. On the one hand, this is being forced by students who are increasingly asking themselves what they will do after they graduate. On the other hand, the constantly changing job market is exerting an ever greater influence on the design of curricula in the academic field, as students are increasingly demanding practical application of the knowledge they have acquired during their studies. Neophilology courses are not spared from this. Students expect their studies – including philology courses – to prepare them to successfully pursue a specific profession. Alongside English, German is proving to be a foreign language relevant to the job market, according to the well-known saying: English is a must, German is a plus! This topic is taken up in Doris Sava and Ellen Tichy‘s recently published anthology by Peter Lang. The volume offers various approaches to the topic outlined in the title. These are practical examples of use and didactic solutions for GFL lessons in the field of specialized languages.